Immune Checkpoint Inhibitor Therapy in Colorectal Cancer—The Role of Cellular Pathology. (September 2021) - Bateman, Adrian C.
Colorectal cancer (CRC) is a common malignancy with a worldwide distribution. Despite bowel cancer screening programmes, the management of patients with metastatic disease is still an important and challenging problem. Immune checkpoint inhibitor (ICI) therapy is a well-established treatment in several cancers, eg, malignant melanoma and non-small cell lung carcinoma and is used in metastatic disease. The principle of this treatment is to use monoclonal antibodies to block the immune tolerance that commonly develops to tumor cells, therefore allowing host T-cell immunity to recognise and lyse cancer cells. The cellular receptors most commonly targeted by ICI therapy are cytotoxic T-lymphocyte-associated protein-4 and the programmed death 1/programmed death ligand 1 system. This review provides a scientific background to current ICI therapy and discusses the factors that predict response to this treatment. This is followed by a description of the emerging evidence for the use of ICI therapy in CRC and the utility of cellular pathology in stratifying patients for this treatment, especially when the systemic disease is present.